2012
DOI: 10.3390/pharmaceutics4040563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced Magnetic Resonance Imaging (DCE-MRI) in Preclinical Studies of Antivascular Treatments

Abstract: Antivascular treatments can either be antiangiogenic or targeting established tumour vasculature. These treatments affect the tumour microvasculature and microenvironment but may not change clinical measures like tumour volume and growth. In research on antivascular treatments, information on the tumour vasculature is therefore essential. Preclinical research is often used for optimization of antivascular drugs alone or in combined treatments. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 140 publications
1
24
0
3
Order By: Relevance
“…This involves intravenously injecting a contrast agent and then monitoring its extravasation over several minutes from a region of interest (Nielsen et al 2012). The focus with these estimates is actually on tumour perfusion, but this may still be an excellent method for identifying tumour hypoxia; oxygen delivery occurs via the vascular supply so the measurements could reflect chronic hypoxia, and changes in perfusion are clearly responsible for fluctuating hypoxia .…”
Section: Exogenous Markers Of Hypoxiamentioning
confidence: 99%
“…This involves intravenously injecting a contrast agent and then monitoring its extravasation over several minutes from a region of interest (Nielsen et al 2012). The focus with these estimates is actually on tumour perfusion, but this may still be an excellent method for identifying tumour hypoxia; oxygen delivery occurs via the vascular supply so the measurements could reflect chronic hypoxia, and changes in perfusion are clearly responsible for fluctuating hypoxia .…”
Section: Exogenous Markers Of Hypoxiamentioning
confidence: 99%
“…MR perfusion and permeability analysis have been applied to characterize a broad range of neoplasms, and their responses to various antiangiogenic and antivascular agents (Choyke, Dwyer, & Knopp, 2003;Leach et al, 2005;Nielsen, Wittenborn, & Horsman, 2012;O'Connor, Jackson, Parker, & Jayson, 2007). The most common application of MR perfusion in oncology has been the evaluation of high-grade primary brain tumors, which typically manifest increased relative BV and increased permeability (Covarrubias, Rosen, & Lev, 2004).…”
Section: Mr Perfusionmentioning
confidence: 99%
“…Another popular technique for monitoring tumour perfusion-related parameters is dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). This involves injecting intravenously a contrast agent and then monitoring its extravasation over several minutes from a region of interest (Nielsen et al 2012). Clinical studies reported that measurements with DCE-MRI correlated with oxygen electrode measurements in cervix (Cooper et al 2000;Lyng et al 2001); pimonidazole binding in head and neck Mayr et al 2010 (b), Mortensen et al 2012 (c), and Li et al 2006 (d) (Newbold et al 2009;Donaldson et al 2011);and [ 18 F]-labelled misonidazole uptake in glioblastoma multiforme (Swanson et al 2009) and head and neck nodal metastases (Jansen et al 2010).…”
Section: Vasculature-based Parametersmentioning
confidence: 99%